1998
DOI: 10.2337/diacare.21.1.42
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Cost of Inpatient Care for Peripheral Vascular Disease, Infection, Neuropathy, and Ulceration in Diabetes

Abstract: Diabetes is confirmed as a significant risk factor for peripheral vascular disease, infection, neuropathy, and ulceration. The severity of these disorders in terms of increased risk of hospital mortality, length of stay, and risk of surgical procedure is also demonstrated for those patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
1
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 14 publications
2
119
1
6
Order By: Relevance
“…27 Individuals with diabetes undergo hospital admission due to PAD, associated infections, and skin ulceration, which are preventable complications of this disease. 28 A meta-analysis has demonstrated that a structured exercise program with duration greater than 30 minutes per session, three sessions per week was associated with a major improvement in maximal walking time for patients with PAD. 29 To date, there have been no randomized clinical trials that prospectively investigate the benefits of smoking cessation and weight loss in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…27 Individuals with diabetes undergo hospital admission due to PAD, associated infections, and skin ulceration, which are preventable complications of this disease. 28 A meta-analysis has demonstrated that a structured exercise program with duration greater than 30 minutes per session, three sessions per week was associated with a major improvement in maximal walking time for patients with PAD. 29 To date, there have been no randomized clinical trials that prospectively investigate the benefits of smoking cessation and weight loss in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…In a large study of unselected diabetic outpatients, skin infections (mainly fungal) were present in 20% of the sample and were the commonest dermatological complaint [55]. In another study analysing the epidemiology of inpatient care resulting from peripheral neuropathy, peripheral vascular disease and skin infections in a UK population of >400 000, diabetic patients had a 6-7 times greater risk of hospitalisation owing to skin and soft tissue infections and related conditions compared to agematched controls [56]. A recent Dutch primary care study that captured medically attended episodes of skin and mucous membrane infections showed odds ratios that were >30% greater for patients with either type 1 or 2 diabetes than for controls after adjustment for potential confounders [57].…”
Section: Skin Nail Mucous Membrane and Soft Tissue Infectionsmentioning
confidence: 99%
“…Diabetic wounds repair very slowly, cause physical inability, and often require amputation. These problems are ultimately caused by poor metabolic control, over time leading to microvascular damage, nerve damage and reduced resistance to infection [1]. Up to the present, healing treatments of diabetic ulcers have not delivered satisfactory results.…”
Section: Introductionmentioning
confidence: 99%